شعرية المكان و حركية الزمان في رواية زارة ... الحب المقدس لمحمد بن زخروفة - ضو, فايزي, ماجدة عائشة (Univercty of Eloued, 2020)
يعتبر فن الرواية من أهم الفنون الأدبية التي عرفت انتشارا في الآونة الأخيرة من خلال وهو ما تجلى في دراستنا المتمثلة في موضوع شعرية ، التعبير عن المضمون الفكري والاجتماعي والهدف من هذا البحث عن المكوناتها ،سّ المكان وحركية الزمان في رواية زارة...الحب المقد ّ وتهدف هذه الدراسة إلى الكشف ، الرئيسة وهي شعرية المكان والزمان في الرواية وكيف تجلت فيها فالمكان يجعل أحداث الرواية أكثر واقعية، عكس الزمان الذي يؤثر في ، عن عناصر العمل الروائي العناصر الأخرى ويكسبها قيمة جمالية. The art of the novel is considered one of the most important Abstract: literary arts that have spread in recent times through the expression of the intellectual and social content, which was evident in our study of the topic of me in the novel of Zara ... sacred love, poetry of place and the dynamism of ti and the aim is to search for its main components, namely Poetics of space and time in the novel and how it was manifested in it, and this study aims to the events of uncover the elements of the fictional work, as the place makes the novel more realistic, unlike the time that affects the other elements and . gives them an aesthetic value
Keywords: شعرية، المكان، الزمان، زارة ...الحب المقد; poetry of place, time, zara ... sacred love